NATO légitámadó-hadművelet Jugoszlávia ellen 1999 - Jakus, János (Közép-Európai Közlemények, 2011)
NATO leadership considered resolving the Kosovo crisis through negotiations by imposing serious threat on the Yugoslav political power. Initially the means of pressure was not identifiable. Analyst suspected political pressure behind the warnings. However, besides political warning, NATO considered the deployment of military force as well. The planners basically calculated with deploying allied air force, since the deployment of ground forces was considered risky, as it could have led to dragging engagement with heavy losses. The concentration of the air force in the region happened quickly and on 24 March, 1999 the bombing began and kept on for 78 days with gradually increasing intensity.